Rancangan Air Traffic Service Route antara VOR “GTL” Gorontalo dan VOR “MKS” Makassar - Christian Adrian Juniartha; Surya Tri Saputra; Eka Justiciana Kusumawati (Jurnal Manajemen Dirgantara, 2024)
The Djalaluddin Gorontalo Airport is the main gateway facility for air transportation that connects Gorontalo province with other regions. Air navigation services at Djalaluddin Gorontalo airport are organized by Perum LPPNPI Gorontalo Sub-Branch. Djalaluddin Gorontalo Airport serves various flight routes to and from Gorontalo. One of the flight routes served is the Makassar - Gorontalo - Makassar flight route. In providing air traffic services and handling the flight, there is no route connecting Makassar and Gorontalo so the W32 route is used. Route W32 is an ATS Route that is frequently traveled by flights to and from various destinations. The use of the W32 route by flights on the Makassar - Gorontalo - Makassar route creates problems in the form of potential conflicts, complexity and traffic density on the W32 route. Alternatives to the use of the W32 route with direct routing is often an option for ATC and pilots but it raises safety issues because direct routing does not have the protection against obstacles and terrain provided by an ATS route. Research was conducted with the aim of overcoming these problems. The method used was Level 1 research and development (RnD) method. The RnD method was chosen to design an ATS route that suits the needs of users at Perum LPPNPI Gorontalo Sub-Branch and Perum LPPNPI MATSC Main Branch. The results showed that creating a new ATS route can be the answer to the problems that occur and accommodate the UPG - GTO - UPG route.